الرقابة القضائية في ظل الظروف الإستثنائية طبقا للمشرع الجزائري - ســـــــاري, نصــــر ابراهيـــــم; زاوي, مبــــــــــاركــــــــــة (University of Eloued جامعة الوادي, 2023)
إن السلطات الإدارية تخضع فيما تصدره من قرارات إدارية و أعمال مادية للقانون، أي تخضع للقواعد القانونية، وعليها أن تحترم هذه القواعد، وأن الخروج على هذا المبدأ يجعل من أعمالها غير مشروعة وتقع تحت طائلة البطلان، وإلا كانت عرضة للإلغاء القضائي وسببا في مطالبة الجهة المصدرة لها بالتعويض عن الأضرار المادية والمعنوية التي نجمت عنها. و الإدارة قد تواجهها في بعض الأحيان ظروفا استثنائية مثل الكوارث الطبيعية أو الفتن الداخلية او الحروب أو مخاطر جسيمة تهدد كيانها ومؤسساتها مما يلزمها الخروج عن سلطاتها الممنوحة لها في الظروف العادية واتخاذ التدابير اللازمة لمجابهة هذه الظروف ولدرء الخطر بحيث تؤدي بها إلى وقف العمل بقواعد المشروعية العادية واستبدالها بقواعد أخرى تتناسب وطبيعة الظرف الإستثنائي، وذلك بهدف حماية النظام العام وحسن سير العمل في المرفق العام. فقد يمس ذلك بالحقوق والحريات العامة عندما تتعسف الإدارة في إستعمالها لهذه السلطة، مما يستوجب على المشرع وضع ضمانات حقيقة وفعالة لحماية هذه الحقوق والحريات من جهة والقيام بأليات وقائية على أعمال الإدارة من جهة أخرى تتمثل في الرقابة بمختلف أنواعها وأشكالها، وهذا هو موضوع مذكرتنا اليوم بحيث تتمثل أهمية الموضوع في دور الرقابة القضائية على أعمال الإدارة في الظروف الإستثنائية حيث تعتبر أهم وأنجع رقابة في هذا المجال لما يتمتع به القضاء من صفات الإستقلال والحياد والموضوعية، وهي بمثابة أقوى الضمانات لهذه الحقوق والحريات. مما يدعنا الى طرح الإشكالية التالية: ما وما مدى جدوى الرقابة القضائية على أعمال الإدارة في ظل سريان الحالات الإستثنائية ؟ للإجابة على هذه التساؤلات قمنا بتقسيم العمل إلى فصلين إثنين هما: الفصل الأول خصصناه لدراسة الإطار المفاهيمي للرقابة القضائية والظروف الإستثنائية، أما الفصل الثاني فخصصناه لدراسة أثر الظروف الإستثنائية في رقابة القاضي على أعمال الإدارة. خلصنا في الفصل الأول إلى أن قرارات الإدارة تخضع في الظروف الإستثنائية لرقابة القضاء الإداري وهي رقابة تأخذ بعين الإعتبار طبيعة الظرف الإستثنائي ومدى الحاجة إلى اتخاذ اجراءات إدارية استثنائية تحقق المصلحة العامة، لذلك تختلف مدى رقابة القضاء الإداري على مشروعية القرارات الإدارية في ظل الظروف الإستثنائية من ركن لآخر، وأن القاضي عموما عند قيامه بممارسة هذه الرقابة على اعمال الإدارة سواء في الحالات الإستثنائية او العادية، لا بد له من احترام الضمانات التي وضعها له المشرع من اجل الوصول إلى المحاكمة العادلة التي تجسد فكرة دولة القانون. أما الفصل الثاني فعرفنا فيه أن رقابة القاضي على أعمال الإدارة في ظل هذه الظروف تترواح بين الضيق والإتساع بحسب الظرف الإستثنائي، ففي حالتي الطوارئ والحصار يبسط القاضي رقابته على أعمال الإدارة باعتباره ما تقوم به في هذه الحالة يعد من قبيل الأعمال العادية، اما في الحالة الإستثنائية فقد تضاربت الآراء بين مؤيد ومعارض حول اعتبار قرارات الإدارة تقبل الطعن أمام القضاء أم انها من أعمال السيادة لا تقبل الطعن القضائي ولا تخضع لرقابة القضاء وهو ما أحذ به المشرع الجزائري من خلال نصي المادتين 98 و 142 من التعديل الدستوري الجديد لسنة 2020، في حين نجده نص على إمكانية إبداء الرأي من طرف المحكمة الدستورية بالنسبة لأعمال الإدارة في الحالة الإستثنائية. أما في الحالة التي لا تخضع فيها الإدارة إلى الرقابة على أعمالها هي حالة الحرب على اعتبار ان ما تقوم به من إجراءات وتدابير في هذا الظرف أساسه مواجهة الأزمة التي حلت بالبلاد ومن واجبها اتخاذ الإجراءات والتدابير على سبيل السرعة والإستعجال من أجل درء الخطر الذي يهدد البلاد من جهة والحفاظ على الأمن والنظام العام من جهة ثانية وأن اهمية الدولة اسبق من الحفاظ على القانون. كما أعطى المشرع وسائل قانونية لممارسة هذه الرقابة تتمثل في دعوى الإلغاء عندما يكون هناك أثر على المراكز القانوني للأفراد، ودعوى التعويض متى نتجت أضرارا من جراء أعمال الإدارة. وفي الأخير خلصنا إلى ان هذا النوع من الرقابة هي رقابة فعالة وناجعة على الهدف منها تطبيق مبدأ المشروعية والحفاظ على الحقوق والحريات العامة والنظام العام في ظل الظروف الإستثنائية. كما أنها تمكن الأفراد من مساءلة الإدارة من خلال دعوى الإلغاء ودعوى التعويض لإستيفاء حقوقهم وتعويضهم عن الأضرار التي لحقت جراء أعمال الإدارة في ظل هذه الظروف.The administrative authorities are subject, in terms of administrative decisions and material actions, to the law, i.e. they are subject to the legal rules, and they must respect these rules, and deviating from this principle makes their actions illegal and subject to nullity, otherwise they are subject to judicial cancellation and a reason for the issuing authority’s claim It shall be compensated for the material and moral damages that resulted from it. And the administration may sometimes face exceptional circumstances such as natural disasters, internal strife, wars, or grave dangers that threaten its entity and institutions, which necessitates it to deviate from its powers granted to it in normal circumstances and take the necessary measures to confront these circumstances and avert the danger so that it leads it to stop working with the rules of normal legitimacy And replacing them with other rules commensurate with the nature of the exceptional circumstance, with the aim of protecting public order and the proper functioning of the public facility. This may affect public rights and freedoms when the administration abuses this power, which requires the legislator to put in place real and effective guarantees to protect these rights and freedoms on the one hand, and to implement preventive mechanisms on the work of the administration on the other hand, which is represented in the various types and forms of censorship, and this is the subject of our memorandum today so that The importance of the subject is represented in the role of judicial oversight over the work of the administration in exceptional circumstances, as it is considered the most important and effective oversight in this field because of the characteristics of the judiciary’s independence, impartiality and objectivity, and it is the strongest guarantee for these rights and freedoms. Which leads us to pose the following problem: What is the feasibility of judicial oversight over the work of the administration in light of the exceptional cases? To answer these questions, we divided the work into two chapters: The first chapter was devoted to studying the conceptual framework of judicial oversight and exceptional circumstances, while the second chapter was devoted to studying the impact of exceptional circumstances on the judge’s oversight of the administration’s work. In the first chapter, we concluded that the administration’s decisions are subject, in exceptional circumstances, to the control of the administrative judiciary, which is an oversight that takes into account the nature of the exceptional circumstance and the extent of the need to take exceptional administrative measures that achieve the public interest. To another, and that the judge, in general, when exercising this control over the work of the administration, whether in exceptional or ordinary cases, must respect the guarantees that the legislator has set for him in order to reach a fair trial that embodies the idea of the rule of law. As for the second chapter, we learned in it that the judge’s oversight of the administration’s work under these circumstances ranges from narrow to wide according to the exceptional circumstance. There have been conflicting opinions between supporters and opponents about whether the administration’s decisions are subject to appeal before the judiciary, or that they are acts of sovereignty that do not accept judicial appeal and are not subject to judicial oversight, which is what the Algerian legislator advocated through the texts of Articles 98 and 142 of the new constitutional amendment of 2020, while we find it It stipulates the possibility of expressing an opinion by the Constitutional Court regarding the work of the administration in the exceptional case. As for the case in which the administration is not subject to supervision over its actions, it is a state of war, given that the actions and measures it takes in this circumstance are based on confronting the crisis that has befallen the country, and it is its duty to take measures and measures as a matter of speed and urgency in order to avert the danger that threatens the country from On the one hand, maintaining security and public order on the other hand, and that the importance of the state takes precedence over preserving the law. The legislator also gave legal means to exercise this control, represented in the lawsuit for cancellation when there is an impact on the legal positions of individuals, and the lawsuit for compensation when damages resulted from the actions of the administration. Finally, we concluded that this type of censorship is effective and efficient, with the aim of applying the principle of legality and preserving public rights and freedoms and public order under exceptional circumstances. It also enables individuals to hold the administration accountable through a claim for revocation and a claim for compensation to fulfill their rights and compensate them for the damages incurred as a result of the administration's actions under these circumstances.
مذكرة ماستر
Keywords: الرقابة القضائية، الظروف الإستثنائية، أعمال الإدارة، دعوى الإلغاء، ودعوى التعويض.; Judicial oversight, exceptional circumstances, management actions, cancellation lawsuit, and compensation lawsuit.